A30P α-Synuclein interferes with the stable integration of adult-born neurons into the olfactory network - Neuner, Johanna (Nature Publishing Group, 2014)
Impaired olfaction is an early symptom in Parkinson disease (PD), although the exact cause is as yet unknown. Here, we investigated the link between PD-related mutant α-Synuclein (α-SYN) pathology and olfactory deficit, by examining the integration of adult-born neurons in the olfactory bulb (OB) of A30P α-SYN overexpressing mice. To this end, we chose to label one well-known vulnerable subpopulation of adult-born cells, the dopaminergic neurons. Using in vivo two-photon imaging, we followed the dynamic process of neuronal turnover in transgenic A30P α-SYN and wild-type mice over a period of 2.5 months. Our results reveal no difference in the number of cells that reach, and possibly integrate into, the glomerular layer in the OB. However, in mutant transgenic mice these new neurons have a significantly shortened survival, resulting in an overall reduction in the addition of neurons to the glomerular layer over time. We therefore propose unstable integration and impaired homeostasis of functional new neurons as a likely contributor to odour discrimination deficits in mutant α-SYN mice.